Sustainable Biocatalytic Procedure for Obtaining New Branched Acid Esters - María Claudia Montiel (MDPI AG, 2021)
Biocatalytic synthesis of 2-ethylhexyl 2-methylhexanoate is described in this work for the first time. This branched-chain ester is suitable for use at low temperatures in numerous applications. The immobilized lipase Novozym® 435 has demonstrated its ability to catalyze the ester synthesis from 2-ethylhexanol and 2-methylhexanoic acid in a solvent-free medium. The high reaction times that are required result in a loss of alcohol by evaporation, which must be compensated for with an excess of this substrate if high conversions are to be achieved. Therefore, two strategies are established: 70 °C with a 10% excess of alcohol, which requires a longer operating time and provides conversions of 97%, and 80 °C with a 20% excess of alcohol, which allows for the achievement of a 99% conversion in a shorter time. The optimal reaction conditions have been chosen based on reusability of the enzyme, process productivity, green metrics and preliminary economic study. When the synthesis is carried out under the best conditions (70 °C, 10% molar excess of alcohol and six uses of the immobilized enzyme) a productivity of 203.84 kg product × kg biocatalyst−1 is attained. The biocatalytic procedure matches many of the objectives of “green chemistry” and is suitable to be scaled up and used in industrial manufacturing.